A prática da promoção, proteção e apoio ao aleitamento materno na perspectiva de equipes gestoras da atenção primária à saúde - Baldan, Juliana de Moraes (Universidade Federal de São Carlos, 2014)
Breastfeeding offers many benefits for mother, baby and Family. Its influence on child and women s health has been the focus of governmental campaigns and programs on national and global scale. The Brazilian Public Health Care System (SUS) develops initiatives to promote, protect and support Breastfeeding on health services. On primary health care, the Family Health Strategy Program has expanded the access to health care and to Breastfeeding initiatives. Health Care Networks were created to promote full care to patients. In São Paulo state, 17 Regional Health Care s Networks were implemented, organized and systematized starting from Primary Health Care Program. São Carlos city belongs to Regional Health Care s Network of number 13. The Primary Health Care Program acts as coordinator assuring full care s implementation on Regional Health Care Networks. Brazil has already programs to support Breastfeeding, but prevalence rates are below World Health Organization s expectation. Breastfeeding s success goes beyond health practitioner s individual performance. Among others aspects, there is also the responsibility of the Brazilian Public Health Care Manager, his initiatives and services on proposing, executing and following the strategies aimed to Breastfeeding. Starting from the assumptions that PHCP is the coordinator of network full care, that care and management are connected on FHSP performance and that higher education s professional teams of São Carlos USF (S) are responsible for create and manage Breastfeeding s care; this study proposes to analyze Breastfeeding s promotion, protection and support on PHCP according to the USF of São Carlos management team. It is a qualitative exploratory research where group interviews were used as data collection. The individuals were nurses, doctors and dentists responsible for executing and managing PHCP's strategies and policies. The data analysis was executed through ALCESTE software. Two thematic blocks were created: Aspects that hamper Breastfeeding , which includes the first class Early weaning's determinants and "Aspects that potentiate Breastfeeding divided in two classes: Aid and network's support to Breastfeeding and The management of Breastfeeding's care . It was evident that, even if the teams have reported the development of actions and orientations for mothers and families about Breastfeeding's practice, they have also evidenced certain impotence and frustration in front of mother's non compliance. They recognized the importance of the articulation with other health sectors, the relevance of professional updates and team meetings on care production and management. It is relevant that Breastfeeding s promotion, protection and support need to be intersectional in order to promote more resolute, humanized and full care.
Keywords: Amamentação; Atenção primária à saúde; Saúde da família; Políticas públicas; Breastfeeding; Primary health care; Family health; Public policies; CIENCIAS DA SAUDE::ENFERMAGEM